Perineural Invasion in Adenoid Cystic Carcinoma of the Salivary Glands: Where We Are and Where We Need to Go - Liu, Xiaohao; Yang, Xiaojun; Zhan, Chaoning; Zhang, Yan; Hou, Jin; Yin, Xuemin (Frontiers in Oncology, 2020)
Adenoid cystic carcinoma of the salivary gland (SACC) is a rare malignant tumors of the head and neck region, but it is one of the most common malignant tumors that are prone to perineural invasion (PNI) of the head and neck. The prognosis of patients with SACC is strongly associated with the presence of perineural spread (PNS). Although many contributing factors have been reported, the mechanisms underlying the preferential destruction of the blood-nerve barrier (BNB) by tumors and the infiltration of the tumor microenvironment by nerve fibers in SACC, have received little research attention. This review summarizes the current knowledge concerning the characteristics of SACC in relation to the PNI, and then highlights the interplay between components of the tumor microenvironment and perineural niche, as well as their contributions to the PNI. Finally, we provide new insights into the possible mechanisms underlying the pathogenesis of PNI, with particular emphasis on the role of extracellular vesicles that may serve as an attractive entry point in future studies.